1997
DOI: 10.1101/gr.7.5.522
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of the γ-Glutamyl Transferase Genes and Other Low Copy Repeats in Human Chromosome 22q11

Abstract: A clone map consisting of YACs, cosmids, and fosmids has been constructed covering low copy repeat regions of human chromosome 22q11. A combination of clone restriction digest analysis, single-copy landmark content analysis, HindIII–Sau3AI fingerprinting, and sequencing of PCR products derived from clones was required to resolve the map in this region. Seven repeat-containing contigs were placed in 22q11, five containing γ-glutamyl transferase (GGT) sequences described previously. In one case, a single interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…The gene transcription is controlled by multiple promoters. Related gene sequences that are either nonfunctional or represent pseudogenes are found in chromosomes 18,19, and 20 (6,7). The multiple promoters and the alternative splicing are responsible for diversity of molecular forms and tissue specificity.…”
Section: Background Informationmentioning
confidence: 99%
“…The gene transcription is controlled by multiple promoters. Related gene sequences that are either nonfunctional or represent pseudogenes are found in chromosomes 18,19, and 20 (6,7). The multiple promoters and the alternative splicing are responsible for diversity of molecular forms and tissue specificity.…”
Section: Background Informationmentioning
confidence: 99%
“…However, Pawlak et al (1988) showed that at least four genes containing GGT sequences were present in the human genome. These are located at band q11 on chromosome 22 (Morris et al, 1993;Collins et al, 1997). Recently, It has been reported that the human GGT was encoded by a multigene family including at least seven genes.…”
Section: Yardimci 2000)mentioning
confidence: 99%
“…A further advantage of 22qDS is the capability of molecular testing for the 22q11.2 deletion, both to identify this subgroup with elevated genetic risk for schizophrenia and to characterize the specific predisposing DNA alteration (primary genetic lesion). Chromosome 22 was the first chromosome to be "sequenced," and its interesting genomic structure [23,24] has intrigued researchers attempting to understand the non-Mendelian genetic mechanisms that may underlie the 22qDS phenotype.…”
Section: Research Advantagesmentioning
confidence: 99%